Asthma deaths in North Carolina: 1999–2016. (3rd May 2020) - Kearney, Gregory D.; Wooten, William; Mohan, Arjun; Christopher Carter, J.; Jones, Katherine; Blount, Theresa; O'Brien, Kevin
Abstract: Introduction: Despite the significant decline in overall death rates in the U.S. over the past decade, many asthma deaths could have been avoided. Eastern North Carolina (N.C.) is an economically challenged region with significant health disparities and a high prevalence of asthma. Objective: The primary purpose of this project was to examine trends of asthma deaths across N.C. and identify counties in the state with the highest mortality rates over an 18-year period. Methods: CDC WONDER was used to query and evaluate age-adjusted asthma mortality rates from 1999 to 2016 among residents in N.C., greater than 1 year of age. Asthma death data were derived from death certificates using ICD-10 underlying cause-of-death codes J45 (asthma) and J46 (status asthmaticus). The Join point regression program was used to test statistical significance in age-adjusted rates for the U.S. and N.C. over the entire study period. Results: N.C. experienced a total of 2, 066 decedents assigned as the underlying cause of deaths for an overall death rate of 12.5 per 1, 000, 000 persons. Death rates were highest among females (14.6 deaths per 1, 000, 000) and black or African Americans (24.7 per 1, 000, 000). Discussion: Overall asthma mortality rates in N.C. decreased. However, several rural and impoverished counties in eastern N.C. with a large percent of blacks or African-Americans, had the highest asthma death rates in the state. Conclusion: Healthcare providers should remain highly cognizant to provide optimal asthma management, education, and follow-up with asthma patients to help avoid unnecessary asthma related deaths.